Empowering Aid Personnel That Respond to Disasters - Vedat Işıkhan (Doğal Afetler ve Çevre Dergisi)
All over the world, the negative consequences of disasters are increasing day by day. While disasters affect millions of people globally each year, unfortunately they also accelerate the inequality and injustice in the society. The frequency of disasters and their impact on people has increased due to climatic changes and increasing population density. Today, earthquakes, floods, drought, fires, volcanic and nuclear explosions, terrorist attacks have turned into ordinary events. Accordingly, the literature on the effects of natural or man-made disasters on victims and communities is abundant. Our findings from the disaster mental health literature indicate that the rescue team that performs the first responders has a risk for negative psychological consequences as they are directly and continuously exposed to traumatic experiences after intervening in disasters. Aid personnel (search and rescue team, firefighters, support groups, etc.) who immediately respond to disasters and assist victims may face various problems after disaster. However, it has been determined that the studies in the literature on the effects of disasters and disasters on these aid personnel are limited. The following study discusses the disaster literature, the relationship of disaster mental health, the general consequences of disasters, the psycho-social, physical and behavioral effects of disasters and disasters on aid personnel, their symptoms, and how to help and strengthen these personnel.